History of the creation of the Conservation Unit Refúgio de Vida Silvestre Serra da Fortaleza in the South of Goiás (Research, Society and Development, 2021)
Conservation units are important spaces for the preservation of biodiversity in a given location, especially in the most threatened, such as the phytogeographic domain of the Cerrado. The history of the creation of a conservation unit, in addition to being essential and a right of citizens in a given region, can also serve as a subsidy and support for other regions to use as a model. In this sense, this research aimed to describe the process of creation of the Wildlife Refuge Conservation Unit Serra da Fortaleza, in Quirinópolis, Goiás. The data survey was carried out with subsidy in documents made available by the Municipal Environment Department of Quirinópolis and interviews. The creation of the UC RVSSF was due to a set of actions mobilized by a group of rural property owners when allocating the legal reserve jointly to an area as an extra-property legal reserve; for the continuous action of the Public Ministry's servers with the Executive Power to carry out the commitment signed in the TAC and the contribution of researchers from UEG, Câmpus Sudoeste, Sede Quirinópolis, together with servers from the Municipal Secretariat for the Environment and Water Resources. The creation procedures followed the precepts subsidized by the current environmental legislation. This unit is an important strategy to ensure the maintenance of a rich biodiversity of one of the most threatened ecological heritages in the world. The relevance of its creation becomes even greater as it is the first conservation space in Goiás in the category of Wildlife Refuge.